Anthropogenic Influences on Dissolved Organic Matter in Three Coastal Bays, North China - Li, Penghui; Zhao, Chen; Liu, Ke; Xiao, Xiaotong; Wang, Yujue; Wang, Yuntao; He, Ding (Frontiers in Earth Science, 2021)
Coastal bays bear anthropogenic influence strongly, and thus dissolved organic matter (DOM) in coastal bays, which is an important component of global carbon cycling, could be heavily affected by anthropogenic inputs. Utilizing absorbance, fluorescence spectroscopy, and stable carbon isotope (δ13C), this study analyzed the characteristics and distribution of DOM in three coastal bays (Jiaozhou Bay, Sishili Bay, and Taozi Bay), located in North China. The results showed that there was always a high concentration of DOM near the river mouth in all three bays and the DOM concentration decreased along the salinity gradient in Jiaozhou Bay, indicating the riverine inputs are the main factor that causes the variation of DOM in these coastal bays. The effects of inflowing rivers on DOM in coastal bays differed with their watershed characteristics (i.e., agricultural/urban). In addition, humic-like DOM components were found to be positively correlated with the apparent oxygen utilization (AOU), suggesting microbial activities could contribute to the DOM in this region. There was generally a higher averaged concentration of fluorescent DOM in surface water than that in bottom water in Jiaozhou Bay. In contrast, higher humic-like DOM was found in bottom water than that in surface water in Sishili Bay and Taozi Bay, which could be attributed to aquaculture activities and biological production. Moreover, photodegradation/photobleaching, dumping, and sewage discharge had their effects on DOM in coastal bays. This study demonstrates that DOM in coastal bays is regulated by multiple sources (rivers, aquaculture, dumping, and sewage) and processes (biological production and photodegradation), and anthropogenic activities have their influences on optical and isotopic characteristics of DOM in coastal bays.